2007
DOI: 10.1038/sj.bjc.6604151
|View full text |Cite
|
Sign up to set email alerts
|

Use of NSAIDs, smoking and lung cancer risk

Abstract: We investigated the risk of lung cancer in relation to non-steroidal anti-inflammatory drugs (NSAIDs) among 573 cases and 857 sex-and age-matched controls for whom we had information on use of NSAIDs, from a prescription database covering all pharmacies in Denmark since 1995, and self-reported NSAID use, smoking habits and other potential confounders. Associations were expressed as odds ratios, assessed by logistic regression in unmatched analyses. After controlling for smoking habits, length of education and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…The self-reported information on NSAID use at study baseline enabled us to evaluate drug exposure prior to the study period; however, we had no information on duration of use before enrollment. A comparison of selfreported use and prescription records revealed that of individuals filling two or more prescriptions for aspirin within one year prior to enrollment, 98% reported aspirin use at enrollment, indicating good reliability of the questionnaire to capture aspirin use [56]. Although we adjusted for a wide range of established CRC risk factors, we cannot rule out confounding by unmeasured factors associated with both NSAID use and CRC risk.…”
Section: Discussionmentioning
confidence: 96%
“…The self-reported information on NSAID use at study baseline enabled us to evaluate drug exposure prior to the study period; however, we had no information on duration of use before enrollment. A comparison of selfreported use and prescription records revealed that of individuals filling two or more prescriptions for aspirin within one year prior to enrollment, 98% reported aspirin use at enrollment, indicating good reliability of the questionnaire to capture aspirin use [56]. Although we adjusted for a wide range of established CRC risk factors, we cannot rule out confounding by unmeasured factors associated with both NSAID use and CRC risk.…”
Section: Discussionmentioning
confidence: 96%
“…20 The use of NSAIDs was also linked to the protective effects against cancers in other sites such as breast, esophagus, stomach, lung, prostate and ovary. [21][22][23][24][25][26][27][28][29] However, the results for these cancer types are less consistent compared to those for colorectal cancer.…”
Section: Nsaids and Cancer Chemopreventionmentioning
confidence: 99%
“…However, reported results of aspirin use and lung cancer risk are conflicting, with both protective [13][14][15][16][17][18][19][20][21] and null effects [22][23][24][25][26][27][28][29][30][31][32] being reported. Three clinical trials focusing on chemoprevention with aspirin reported non-significant protective effects [35][36][37], and a recent pooled analysis of individual-level data from 7 clinical trials of daily aspirin reported a protective effect on lung cancer death, with a protective latent period of about 5 years.…”
Section: Discussionmentioning
confidence: 99%